1993
DOI: 10.1017/s0263574700019342
|View full text |Cite
|
Sign up to set email alerts
|

Robotics for health care: a review of the literature

Abstract: This paper surveys the scientific literature on present and future applications of robotics to health care. The term ‘health care’ refers to different forms of assistance rendered to people who are unable without such assistance to perform physical tasks that ‘healthy’ people accomplish unaided. Research efforts and accomplishments to date are concentrated in four main application areas: rehabilitation; patient transfer; assistance to surgery; and ‘microrobots’ suitable for use inside people. Some initial work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Various studies have discussed the importance of automation and robotics in care facilities [8]. The earliest noticeable discussion was by Kassler [9], where the potential of robots in assisting and giving services to users was envisioned as the next era for health care. This resulted in the development of multiple scenarios in which robots provide various services to help patients [1], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have discussed the importance of automation and robotics in care facilities [8]. The earliest noticeable discussion was by Kassler [9], where the potential of robots in assisting and giving services to users was envisioned as the next era for health care. This resulted in the development of multiple scenarios in which robots provide various services to help patients [1], [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, popular opinion holds that robotic technologies are only applied to individuals when they are disabled [10]. However, there is a small yet increasing awareness that robotic technologies can also complement current health care service provision by monitoring older people within their home environment [11] and assisting them to mobilise safely and prevent falls [12]. Narrative literature reviews on the role of robotics in health care [8, 1113] or social assistance robots [14] have previously been completed mainly speculating about the future of robotics in health.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of practice plays an important role in motor recovery for stroke patients based on the experience from the conventional therapy in stroke rehabilitation and the motor learning theory [50]. Compared with conventional therapy, robotic rehabilitation 10 therapy can provide safe and high-intensity rehabilitation to patients with mild to severe impairments after stroke [51]. Recent studies have shown the benefits of robotic rehabilitation therapy on the upper-limb movement of patients in the acute phase of recovery after stroke.…”
Section: Robotic Assistive Therapy In Stroke Rehabilitationmentioning
confidence: 99%